CHANGING PATHS” LATIN AMERICAN UNIVERSITIES GOING VIRTUAL - RAMA, CLAUDIO (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
Present paper analyses the growing process of using and incorporating information and communication technologies in education and how does this process impact in existing models of part time education processes. Resarcher analyses impact of processes, university dynamics and how these are affected by a constant and strong model on going virtual. Hypotesis is presented as  typology of higher education institutions responding ways towards ICT such as re-engineering of online and part time institutions, new offers of college education 100% online, become special subjects of university’s education into online programs and so as online management information trend. Thorough, a comparative analysis we developed a hypothesis of a new and slow online education and vanishing common space between new online education vs. traditional full time education.